Pengaruh Pemberian Angkak Monascus purpureus terhadap Kualitas Mikrobiologis Feses Tikus Putih Hiperlipidemia - T Yulinery; R. Hardiningsih; N. Nurhidayat (Universitas Atma Jaya Yogyakarta, 2010)
Angkak is defined as rice fermented by Monascus purpureus, a lovastatin and pigmen producer. The objective of this research was to observe the effect of angkak powder to the digestion system represented by the quality of faeces. The in vivo bioassay was carried out using 20 Sprague-Dawley strain mice into 5 groups. First group was given angkak respectively 0.01g, 0.1g, 0.5g, and two groups of control (positive and negative). The faeces were examined each week for a month. The number or erytrosit, bacteria, and fungus were examined microscopically. The results showed that 0,01g, 0,1g, 0,5g of angkak did not significantly affect of bacteria, fungus and erythrocyte on faeces. The data suggest that the administration of angkak might be useful and safe for the hypercholestrolemic treatment.